Zehneria subcoriacea (Cucurbitaceae), a New Species from Kenya - Zhou, Ya-Dong; Mbuni, Yuvenalis; Hu, Guang-Wan; Yan, Xue; Mwachala, Geoffrey; Wang, Qing-Feng (Phytotaxa, 2016)
Zehneria subcoriacea Y.D. Zhou & Q.F. Wang, a new species of Cucurbitaceae is described and illustrated here, which is recorded as Zehneria sp. A in Flora of Tropical East Africa. It is easily recognized by its sub-coriaceous leaves and hairy stamens and staminodes.